1977
DOI: 10.1093/ije/6.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations in a Southern Rural Community: an Application of the ‘Ecology Model’

Abstract: The purpose of this study is to re-examine the concepts of health services utilization presented by White and his colleagues in 'The Ecology of Medical Care'. We re-test their model in a rural population in the southern United States using longitudinal instead of cross-sectional data and find that the general principles of the 'Ecology' model do, indeed, apply to rural populations like Rougemont/Bahama. Use of this model has implications for modifying and improving the organization of the health care delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
3
4
1
Order By: Relevance
“…This paper has the added benefit of using a more detailed approach to the ecology of recourse to health care, providing details on the nature of the health care providers, the setting in which that care is provided, and the kind of care received. In line with other observations, 2,4,8,9 our study showed that the vast majority of the population had turned to local health care providers for their health problems, which most often required little or no technical input. This finding may be useful when discussing the distribution of health care resources between the various areas of care, the role of different service providers, and their specific training needs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This paper has the added benefit of using a more detailed approach to the ecology of recourse to health care, providing details on the nature of the health care providers, the setting in which that care is provided, and the kind of care received. In line with other observations, 2,4,8,9 our study showed that the vast majority of the population had turned to local health care providers for their health problems, which most often required little or no technical input. This finding may be useful when discussing the distribution of health care resources between the various areas of care, the role of different service providers, and their specific training needs.…”
Section: Discussionsupporting
confidence: 91%
“…While White's original trials conducted among the Anglo-American population in 1961 showed a rate of 750 people per population of 1000 inhabitants reporting experience of a health problem, 2 more recent studies have revealed figures of between 800 to 860 people per 1000. 4,8 In the present study, slightly fewer than 40% of people who reported experiencing at least one health problem had not turned to any medical professional. This underlines the importance of the self-management of health problems, which includes self-medication, but also recourse to other practitioners outside the health care system.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Fukui et al 2 previously revealed that, compared with data in the United States, people in Japan visited community physicians and hospital-based outpatient clinics more frequently. This ecology model has been replicated over several decades, [3][4][5][6] including from our group, 2,7,8 with findings that were consistent with those of White et al 1 This model has subsequently been widely used by both policy makers and educators. 9,10 Unlike the medical system in the United States, Japan has a universal health care system, which allows virtually free health care access to everyone including children.…”
supporting
confidence: 65%